The Union of Rusyns and Ukrainians of Yugoslavia: creation and first years of activity - Janko Ramach; Galyna Sagan (Cхід, 2018)
The article reveals the activity of the Union of Rusyns and Ukrainians of Yugoslavia (since the late 1990s, the Union of Rusyns and Ukrainians of Serbia and Montenegro), which the organization conducted in the first ten years after its creation (May 12, 1990). For the presentation of those studies, the reports of the fellowship were analyzed, which were published in the periodicals of the Union. Other materials of diaspora's periodicals were also used for the study, which reveals the content of the society's work. The Union was formed with the aim of unifying the Ukrainian and Rusyn community not only of Serbia, but also of all their representatives in the post-Yugoslav space. The organizational work of the Union was aimed at supporting ethnic and cultural traditions of Rusyns, Ukrainians, as well as other representatives of national minorities, especially in Serbia. The community carried out its activity in close cooperation with the diplomatic institutions of Ukraine in Serbia, had active communication with colleagues in Ukraine. Its activity in the 90-ies of the twentieth century, the Union of Rusyns and Ukrainians of Serbia and Montenegro demonstrated tolerance and struggle for the preservation of the rights of all national minorities that inhabit the post-Yugoslav space. In the 90-ies of the twentieth century, through its activities, the Union of Rusyns and Ukrainians of Serbia and Montenegro demonstrated tolerance and struggle for the preservation of the rights of all national minorities that inhabit the post-Yugoslav space.